2012
DOI: 10.1073/pnas.1205828109
|View full text |Cite
|
Sign up to set email alerts
|

Selectively altering belief formation in the human brain

Abstract: Humans form beliefs asymmetrically; we tend to discount bad news but embrace good news. This reduced impact of unfavorable information on belief updating may have important societal implications, including the generation of financial market bubbles, ill preparedness in the face of natural disasters, and overly aggressive medical decisions. Here, we selectively improved people's tendency to incorporate bad news into their beliefs by disrupting the function of the left (but not right) inferior frontal gyrus usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
132
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(147 citation statements)
references
References 15 publications
(21 reference statements)
11
132
2
2
Order By: Relevance
“…It is well established finding in psychological research that people tend to overestimate the likelihood of positive events and underestimate the likelihood of negative events (11)(12)(13)(14)(15)24). For example, people expect to enjoy healthier lives than average or underestimate the probability of being divorced (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established finding in psychological research that people tend to overestimate the likelihood of positive events and underestimate the likelihood of negative events (11)(12)(13)(14)(15)24). For example, people expect to enjoy healthier lives than average or underestimate the probability of being divorced (11).…”
Section: Discussionmentioning
confidence: 99%
“…In old age expectations are adjusted downwards though actual wellbeing is rising. Human belief formation is known to exhibit systematic biases such as optimism (11)(12)(13)(14)(15) and the underestimation of hedonic adaptation to changes in life circumstances (16,17). -How satisfied are you with your life, all things considered?…”
Section: Introductionmentioning
confidence: 99%
“…Although most investigations of unrealistic optimism have taken place within a social-psychological framework, recently there has been growing interest in relevant neural and pharmacological mechanisms (Sharot et al, 2007(Sharot et al, , 2012a(Sharot et al, , 2012b. In a seminal study, Sharot et al (2011) identified right inferior frontal gyrus (IFG), putatively extending into the pars opercularis, as the region of the brain responsible for coding information that should reduce positive expectations; moreover, these authors demonstrated that unrealistic optimism is associated with deficient coding of such information in this region.…”
Section: Introductionmentioning
confidence: 99%
“…We based our power analysis on previous research on the optimistic learning bias Korn et al, 2014;Kuzmanovic et al, 2015;Moutsiana et al, 2013;Sharot, Guitart-Masip, et al, 2012;Sharot, Kanai, et al, 2012;Sharot et al, 2011) Time Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…Updating from good news conforms closely to Bayesian inference, whereas updating from bad news is reduced compared with normative predictions (Eil & Rao, 2011). Moreover, individual differences in optimistic learning track more closely with updating from bad news than good news (Lefebvre, Lebreton, Meyniel, BourgeoisGironde, & Palminteri, 2017;Moutsiana et al, 2013;Sharot et al, 2011), and interventions that alter optimistic learning affect updating from bad news but not good news (Sharot, Guitart-Masip, Korn, Chowdhury, & Dolan, 2012;Sharot, Kanai, et al, 2012). This suggests that increasing concern for others may increase vicarious optimism by reducing updating from bad news.…”
mentioning
confidence: 99%